Ein einfaches analytisches Modell zur Darstellung der atmosphärischen Zirkulation in Europa im Weichsel-Hochglazial - Kottmeier, Christoph; Meyer, Hans-Heinrich (ERDKUNDE, 1988)
An analytical flow model is presented, which describes the atmospheric circulation in Europe during the last (Weichselian) ice-maximum. The model is based on the prescribed mean temperature field in the troposphere, which is estimated from the following glacial parameters: land ice and sea ice distribution and morphology, distribution of terrestrial and marine surfaces, near surface temperatures at different terrain elevations. The know ledge on these parameters is presented. Results of the model application are spatial distributions of the mean geostrophic winds and near surface winds. It is shown, that the Scandinavian ice sheet will have affected the circulation. The concurrence of two flow regimes is significant. In the ultimate vicinity of the ice margin, and in Eastern Europe, easterly and northeasterly winds are documented. In Western Europe westerly winds prevailed.